Pengaruh Mekanisme Corporate Governance Terhadap Ketepatan Waktu Pelaporan Keuangan (Studi Empiris Pada Perusahaan Perbankan Milik Pemerintah Pusat) - Muhammad Rivandi; Maria Magdalena Gea (Jurnal Akuntansi dan Pajak, 2018)
This study aims to examine the effect of corporate governance mechanism on the timeliness of financial reporting. The sample of this study are four central banking companies listed in Indonesia Stock Exchange (IDX) selected based on purposive sampling method. The method of data analysis used in this study is multiple regression models. Based on the hypotheses testing result, that the managerial ownership and audit committee have a positive and significant effect on the timeliness of financial reporting, while independent commissioner has no effect on the timeliness of financial reporting